Evaluating the influence of microstructural attributes: Fraction, composition, size and spatial distribution of phases on the oxidation behaviour of high-entropy alloys. (15th May 2021) - Anupam, Ameey; Ang, Andrew S.M.; Guruvidyathri, K; Abbas, Musharaf; Sivaprahasam, D.; Munroe, Paul; Berndt, C.C.; Murty, B.S.; Kottada, Ravi Sankar
Graphical abstract: Highlights: Oxidation of five HEAs Al1-2 CoCr0.5-1.5 Fe0-1 Ni at 1100 °C by varying Al, Cr, Fe. Al2 CoCrFeNi, AlCoCr0.5 Ni exhibit lowest oxidation rates. Nanoscale Al-rich precipitates act as Al reservoirs to aid protective alumina growth. Optimum size and distribution (KNN) of nanoscale precipitates recommended. Al-lean phase fraction and its Al content predicted by CALPHAD proposed to shortlist oxidation resistant HEAs. Abstract: Oxidation behaviour of five high entropy alloys (HEAs): AlCoCrFeNi, Al2 CoCrFeNi, Al2 CoCr1.5 FeNi, AlCoCrNi and AlCoCr0.5 Ni, has been studied at 1100 °C in the cast-annealed condition. Al2 CoCrFeNi and AlCoCr0.5 Ni HEAs exhibit the lowest oxidation rates of the order of 10 −12 g 2 cm −4 -s −1 . Al-rich nanoscale precipitates are observed to aid protective oxide growth. The Al-lean phase fraction and its Al content also have a major effect on the alloy's oxidation behaviour. A parameter 'X' taking the ratio of these two has been introduced, which coupled with CALPHAD predictions can be a potential tool to shortlist HEAs for oxidation resistance applications.